2022
DOI: 10.3390/cancers14235731
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Drug Resistance in Non-Small Cell Lung Cancer: Where Are We Now and Where Are We Going

Abstract: Lung cancer is the leading cause of cancer-related mortality in the world. The development of drug resistance represents a major challenge for the clinical management of patients. In the last years, microRNAs have emerged as critical modulators of anticancer therapy response. Here, we make a critical appraisal of the literature available on the role of miRNAs in the regulation of drug resistance in non-small cell lung cancer (NSCLC). We performed a comprehensive annotation of miRNAs expression profiles in chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 165 publications
0
1
0
Order By: Relevance
“…They can bind to complementary sequences in 3′untranslated region (3′UTR) in target mRNAs, leading to mRNA translation inhibition or degradation [ 4 ]. Numerous studies have reported that miRNAs are important for tumor occurrence and development, like cell proliferation, apoptosis, migration, stemness, or other malignant processes [ 5 , 6 ]. miRNAs can play a role of oncogenes or tumor suppressors in NSCLC [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…They can bind to complementary sequences in 3′untranslated region (3′UTR) in target mRNAs, leading to mRNA translation inhibition or degradation [ 4 ]. Numerous studies have reported that miRNAs are important for tumor occurrence and development, like cell proliferation, apoptosis, migration, stemness, or other malignant processes [ 5 , 6 ]. miRNAs can play a role of oncogenes or tumor suppressors in NSCLC [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%